The stages of national education system operation: Issues, rationale, and challenges for the Ministry of Education Malaysia (MOE) in facing post pandemic norms of covid-19 - Irma Wani Othman; Saifulazry Mokhtar; Mohd Sohaimi Esa (Global Academic Excellence (M) Sdn Bhd, 2022)
In the context of this paper, the discussion on the operation of the national education system to be implemented in stages is highlighted through the issues, rationale and challenges of Malaysia facing the post-pandemic norms of Covid-19. The objective of this writing is to debate the relationship between the Covid-19 pandemic and the efforts of the education sector in transforming Teaching and Learning sessions. Secondary data analysis methods utilise the acquisition of journals, reports, books, interviews, online news and current printed materials. The findings include (i) New Norms of Education, (ii) Mandatory Student Ownership of e-Learning Devices and Gadgets, (iii) Educator Mastery of Online Learning Delivery Methods, (iv) Accessibility of Digitisation of Education Along with the Demands of Industrial Revolution 4.0 (IR4.0) in Society 5.0, (v) Examination Rescheduling Issues and Fee Payment Rate Reduction, and (vi) Career Prospects of Post-Covid Graduates. The goal of this research looks into (i) the direct impact of school closures created huge learning gaps on children in the country, as well as (ii) rehabilitating the higher education system following the Covid-19 pandemic, enhancing digitalisation of education, empowering up-to-date teacher training, and providing better educational facilities in line with the Covid-19 post-pandemic future education concept.